Dynamics Of Organizational Communication Patterns And Their Implications For The Performance Of Kedondong Village Apparatus - Fajar Istikhomah; Siti Endraswati; Latutik Mukhlisin; Awit Istighfarin (Perspective Humanities and Social Sciences, 2025)
Organizational communication plays an important role in shaping work effectiveness and coordination in public institutions, including village governance. Nevertheless, studies on village administration have largely emphasized leadership and administrative performance, while organizational communication patterns at the village level remain underexplored. This study addresses this gap by examining the organizational communication patterns implemented in the Government of Kedondong Village and their implications for officials’ performance. Using a qualitative descriptive approach, data were collected through semi-structured interviews with six village officials, supported by observation and documentation. The findings show that vertical communication is predominantly top-down and instructive, with limited institutionalized bottom-up feedback mechanisms. Horizontal communication occurs through inter-sectoral technical coordination but is constrained by perceptual differences and varied communication styles among officials. Diagonal communication is frequently used to facilitate task completion; however, it remains informal, undocumented, and highly dependent on individual initiative. This study contributes to organizational communication scholarship by providing empirical insights into communication patterns within grassroots public organizations. It also offers practical implications for public sector governance by highlighting the need to institutionalize more inclusive and structured communication channels to enhance coordination, accountability, and performance in village administration.